2003
DOI: 10.1046/j.1365-313x.2003.01830.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a locus controlling Verticillium disease symptom response in Arabidopsis thaliana

Abstract: SummaryVerticillium dahliae Klebahn is a soil-borne fungal pathogen causing vascular diseases. The pathogen penetrates the host through the roots, spreads through the xylem, and systemically colonizes both resistant and susceptible genotypes. To elucidate the genetic and molecular bases of plant±Verticillium interactions, we have developed a pathosystem utilizing Arabidopsis thaliana and an isolate of V. dahliae pathogenic to both cruciferous and non-cruciferous crops. Relative tolerance (based on symptom seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
175
1
19

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(208 citation statements)
references
References 85 publications
10
175
1
19
Order By: Relevance
“…[See online article for color version of this figure. ] potato (Solanum tuberosum; Zhou et al, 2006;Klosterman et al, 2009). Typical symptoms caused by V. dahliae include leaf necrosis, premature defoliation, altered flowering time, and severe growth stunting (Veronese et al, 2003;Fradin et al, 2009;Xu et al, 2011b). Recent studies have identified signaling pathways that play essential roles in cotton resistance to V. dahliae (Xu et al, 2011b;Gao et al, 2013;Zhang et al, 2013), but how plants orchestrate development under V. dahliae infection remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[See online article for color version of this figure. ] potato (Solanum tuberosum; Zhou et al, 2006;Klosterman et al, 2009). Typical symptoms caused by V. dahliae include leaf necrosis, premature defoliation, altered flowering time, and severe growth stunting (Veronese et al, 2003;Fradin et al, 2009;Xu et al, 2011b). Recent studies have identified signaling pathways that play essential roles in cotton resistance to V. dahliae (Xu et al, 2011b;Gao et al, 2013;Zhang et al, 2013), but how plants orchestrate development under V. dahliae infection remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Susceptible ecotypes exhibit a pathogen-induced early-flowering phenotype, whereas more tolerant ecotypes exhibit delayed flowering after Verticillium spp. inoculation (Veronese et al, 2003;Häffner et al, 2010). It is reported that VET1 (for V. dahliae tolerance) plays a negative role in flowering time and a positive role in pathogen resistance (Veronese et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the growing demand for oil crops as sources for nutritional oils and biofuels, novel strategies to limit the spread of V. longisporum are needed. Since these can be based on the molecular mechanisms of defense responses, several groups have started to investigate the interaction between V. longisporum and the model plant Arabidopsis (Steventon et al, 2001;Veronese et al, 2003;Johansson et al, 2006;Floerl et al, 2010Floerl et al, , 2012.…”
mentioning
confidence: 99%
“…Similarly, a study conducted on two different ecotypes of Arabidopsis (Columbia and Cape Verde Islands) exposed to elevated CO 2 levels revealed that the magnitude of various biological responses, including photosynthesis, starch accumulation, nitrogen content and differential gene expression, varied between the two ecotypes [36]. Ecotypic differences like this are well documented, and have shown to influence flowering time [37], disease resistance [38] as well as oxidative stress tolerance [39], all of which are important aspects of a bioregenerative life support system and potential food source.…”
Section: The Use Of Diverse Genotypes and Speciesmentioning
confidence: 99%